Treatment of Hyperoxia-Induced Lung Injury with Lung Mesenchymal Stem Cells in Mice - Yabo Mei; Chong Chen; Hui Dong; Wanqiao Zhang; Yan Wang; Ming Chi; Zhichun Feng (Hindawi Limited, 2018)
Objective. Bronchopulmonary dysplasia (BPD) is a common chronic lung disease in preterm neonates and has no effective treatment. This study aimed to investigate the therapeutic effects of neonatal mouse lung resident mesenchymal stem cells (L-MSCs) on the hyperoxia-induced lung injury. Methods. L-MSCs were separated and identified according to the MSC criterions. Hyperoxia-Induced Lung Injury (HILI) of neonatal KM mice was induced with hyperoxia (FiO2 = 60%) and investigated with pathological methods. Neonatal KM mice were divided into 3 groups (hyperoxia + L-MSC group, hyperoxia + PBS group, and air control group). Mice in the hyperoxia + L-MSC group were treated with L-MSCs at 3, 7, and 14 days after birth. After hyperoxia exposure for 21 days, the lung pathology, Radial Alveolar Count (RAC), CD31 expression, and vascular endothelial growth factor (VEGF) expression were investigated. Results. After hyperoxia exposure, the body weight, RAC, CD31 expression, and VEGF expression in the hyperoxia + L-MSC group were significantly better than those in the hyperoxia + PBS group but inferior to those in the air control group significantly. These indicate L-MSCs are partially protective on the lung injury of mice with hyperoxia-induced BPD. Conclusion. L-MSCs are helpful for the prevention and treatment of BPD, and endogenous L-MSCs may play a role in the postinjury repair of the lung.